The Effect of Liquidity, Capital Structure and Company Size on Company Value Subsector Food and Beverage - Saputra, Irfan; Matyani, Matyani; Sofyaun, Ashari (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of this study is to determine the effect of Liquidity, Capital Structure and Company Size on Company Value. The data used are secondary data in the form of annual reports and stock price data of Food and Beverage Subsector Companies listed on the Indonesia Stock Exchange for the period 2020-2024. Sample selection was carried out using purposive sampling technique and obtained 19 companies. The year of this study was 4 years so that the total observations were 76 and the data analysis techniques used were classical assumption tests, multiple linear regression, ANOVA tests and t-tests assisted by the IBM SPSS Statistics 25 program. The results of the analysis show that liquidity has no effect on company value. Capital structure has a positive and significant effect on company value. Company size has no effect on Company Value.